Foreign letters [videorecording (DVD)] - Thier, Ela; Thier, Ela; Thier, Ela; Lê, Dalena Thùy-Anh; Rotstein, Noa, 1997- (Film Movement series., 2012)
Ellie, a 12-year-old immigrant girl from Israel, is lonely and homesick. Life brightens when she meets Thuy, a Vietnamese refugee her age. Trust slowly builds as the two teach each other about life in America. As Ellie and Thuy become inseparable, they eventually hurt and betray each other. Ellie must give up her most prized possession, in order to save their friendship.